Localized Lymph Node Light Chain Amyloidosis - Binod Dhakal; Alexandra M. Harrington; Michael E. Stadler; Anita D’Souza (Case Reports in Hematology)
Immunoglobulin-derived light chain amyloidosis can occasionally be associated with localized disease. We present a patient with localized lymph node light chain amyloidosis without an underlying monoclonal protein or lymphoproliferative disorder and review the literature of lymph node amyloidosis discussing work-up and risk factors for systemic progression.